The story of Vietnam a background book on the war in Southeast Asia - Dareff, Hal (New York Parents' Magazine Press, 1971)
Presents the history of Vietnam with emphasis on the recent complex developments and the impact of French and United States involvement.
1
Keywords: Vietnam -- History -- Juvenile literature